PENGEMBANGAN MEDIA “SMART BOARDBOOK” BERBASIS AUGMENTED REALITY PADA TEMA 6 SUBTEMA 1 KELAS II SD NEGERI 104197 DESA KLAMBIR - Nurmayani Nurmayani; Liza Ayu Khairani (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
The purpose of this study was to determine the feasibility and effectiveness of using Augmented Reality-based “Smart Boardbook” media. This research is a development research (Research and Development) which refers to the ADDIE development model which consists of 5 stages, namely the analysis, design, development, implementation, and evaluation stages. The research shows that the augmented reality-based “smart boardbook” media on the theme of 6 sub-theme 1 class II SD that was developed has been validated by a media expert validator in the first stage obtaining a feasibility percentage of 73.80% included in the “feasible” criteria and in stage II obtaining the results of the percentage of eligibility of 95.20% are included in the "very feasible" criteria. And according to the material expert validator in stage I the percentage of feasibility results is 75.55%. included in the "feasible" criteria and in stage II the percentage of eligibility results was 92.22%. included in the "very feasible" criteria. And according to education practitioners, the percentage of eligibility results is 98.18% including the "very feasible" criteria. The results of individual trials and small group trials each get an average score of 1 which is in the "good" category. In the field trial stage, the effectiveness criteria were achieved with the number of students reaching 17 people in the post-test or about 89.47%. Keywords: Augmented Reality, Media, Research Development, Smart Boardbook